PERUMUSAN ADDED VALUE DALAM KONSEP BISNIS COFFEEIN MELALUI PENDEKATAN BLUE OCEAN STRATEGY - Richie Fernaldi (Jurnal Performa)
The coffee industry is a growing industry in Surabaya. As a result, innovation becomes an essential aspect in broadening the existing market. The purpose of this study is to formulate added values for Coffeein in attempt to adapt to the target market. This research is a qualitative research. The population and sample in this study consist of coffee entrepreneurs, Starbucks consumers, and Coffeein consumers. Interview and observation are used to collect research data, while triangulation technique is used to test the validity of the data. The data analysis tool in this study is the Blue Ocean Strategy, which consists of canvas strategy, fourstep framework, value innovation, and added values. Research results conclude that seasonal menu is the added value that needs to be implemented by Coffeein in order to broaden the market.